The Managerial Ombudsman. Issue 4 (24th February 2020) - Gill, Chris; Mullen, Tom; Vivian, Nial
Abstract: This article identifies a major development in the role and practice of the ombudsman. It argues that the New Public Management practices that have transformed public administration in the last 30 years have led to a more managerial approach to the ombudsman's work. The article's argument is developed through analysis of an empirical case study of the Scottish Public Services Ombudsman, which illustrates how the aims and techniques of managerialism have been deployed in the ombudsman context. The article evaluates the significance of these developments for the ombudsman institution and for the wider justice system. It examines the risks and opportunities inherent in this turn to managerialism and whether it represents a departure from the ombudsman's mission or a necessary adaptation to a changed world of public administration. In identifying the rise of the 'managerial ombudsman', the article provides a new framework for conceptualising developments in the modern ombudsman institution.